Pengaruh Variasi Bahan Peredam Kemasan dan Tingkat Kematangan Buah Alpukat terhadap Tingkat Kerusakan Mekanis pada Simulasi Getaran Selama Transportasi - Rahmah, Fadhlilla Monica; Tamrin, Tamrin; Rahmawati, Winda; Kuncoro, Sapto (abe.fp.unila.ac.id, 2023)
Cause of damage is improper or inappropriate packaging. Therefore this study aims to determine the optimal type of packaging damper in minimizing mechanical damage to the fruit. This research was conducted in February - April 2020 at the Laboratory of Bioprocess Engineering and Postharvest Handling, University of Lampung. This research was conducted by looking at the level of damage to the avocado when dropped manually and when vibrated mechanically with a vibrating table. In the manual experiment, one avocado is divided into four parts, each part will be treated with different absorbent materials in the form of straw, fibers, dried banana leaves and control with a thickness of 2cm damper which is then dropped from a height of 5 cm, 10 cm, and 15 cm. In mechanical testing using a packaging box measuring 29 cm long, 14 cm wide and 14 cm high. Each box contains 12 avocados arranged in 2 layers and then added with a damper with a thickness of 2 cm, each package is ventilated with a circle type with a diameter of 3 cm, 4 pieces on each right and left side of the package. The observed parameters were mechanical damage in the form of bruises, weight loss, and level of hardness test. The observed data obtained were processed using simple statistics with each data averaged and compared to the damage between the fruit that was dropped manually and vibrated with a vibrating table. The results showed that the fiber-absorbing agent treatment was more optimal in minimizing mechanical damage to avocado because the fibers had a lignin content of around 29.4%. Keywords: Avocado, Mechanical Damage, Silencer, Transportation Simulation.